Implementasi Sistem Informasi Manajemen Inventaris Berbasis ERP Odoo 17 pada PT XYZ - Lim Jong Su (Ikatan Ahli Informatika Indonesia, 2025)
PT XYZ is an agribusiness company engaged in the provision of cassava products and fertilizers, with a commitment to supporting sustainable agricultural practices. The main problems faced include stock recording, fertilizer procurement, and coordination of cultivation activities, which are still carried out manually using notebooks and basic spreadsheets. This condition often leads to data duplication, delays in stock updates, and discrepancies between physical stock data and administrative records. This study aims to design and develop an inventory management information system based on ERP Odoo 17 using the Prototyping Model approach. The system is designed to integrate three main modules—Inventory, Purchase, and Agriculture Management—which are interconnected to support centralized, automated, and real-time business processes. The methods used include data collection techniques such as in-depth interviews with the Warehouse Head, Procurement Staff, and Operations Manager, direct observation of stock management processes, and literature review on ERP implementation in the agribusiness sector. The resulting system prototype is capable of recording goods in and out, performing stock adjustments, supporting purchase requests through to goods receipt from vendors, and digitally recording cassava cultivation activities. With inter-module relationships, every data input in one module is automatically updated in the other modules, thereby minimizing the risk of data redundancy.